Eksplorasi Penggunaan Media Ular Tangga Edu-Qur’an Sebagai Strategi Pembelajaran Literasi Qur’an - Erlin; Eka Safitri; Moh.Hafizh Abdulloh; Aida Wafiq Nahda; Dika Bayu Sigit Prabowo; Dimas Arga Sadewa; Irfanda Kurniawan; Metta audhya gotami; Putri Lestari; Rafika Ferdiana Ristanti; Sonia Rahma Laila; Eric Khanafi Ihsana; Fadillah Dea Ramadan; Linda Ikawati (STAI AL-AMIN, 2025)
This study aims to explore the use of the Edu-Qur'an Snakes and Ladders media in learning Qur'an literacy in grade 4 of Mranggen Tengah Elementary School, Bansari District, Temanggung Regency. The method used is qualitative with observation and interviews with students. The results of the study showed that this media received a positive response, with 8 students feeling very happy and 4 students feeling happy. This game-based learning succeeded in creating a pleasant atmosphere, increasing students' motivation to be more active in learning Qur'an material, such as hijaiyah letters, tajwid, and short surahs. Students expressed a desire to play this game again and gave suggestions to enlarge the game board, increase the number of questions, and increase the level of difficulty. This study suggests the development of media by adjusting the level of difficulty of the questions and adding reward elements to be more effective in improving Qur'an literacy in elementary schools.Keywords: Bullying, Students, Impact, Achievement.